Efficiency of cognitive-behavioral group therapy for obesity in combination with dietary modifications in women - S. O. Eliashevich; A. P. Misharova; A. V. Orekhova; Ya. V. Medik; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Data are accumulating on the direct influence of psychoemotional and psychosocial factors on the inexorable growth of obesity prevalence, and therefore the concept of an interdisciplinary approach is needed, including dietary, physical activity and mental state modifications.Aim. To determine the effectiveness of cognitive-behavioral group therapy (CBGT) in combination with nutritional modifications for body mass (BM) management in women with obesity.Material and methods. The study involved 20 women (mean age 46,6±12,3 years) with a BMI ≥30 kg/m2, rigid to diet therapy. A medical psychologist and a nutritionist conducted CBGT sessions with the participants. Initially, BM, BM index, and eating behavior were assessed (DEBQ, Stunkard, CARDIA questionnaires). In addition, the following were used to study the mental status: Toronto Alexithymia Scale (TAS-20), vital exhaustion test, University of California, Los Angeles (UCLA) Loneliness Scale, Test of Self-Conscious Affect (TOSCA), Reeder Stress Inventory, and Psychological Stress Measure (PSM-25). The changes were studied 8 weeks after the start CBGT.Results. After 2 months, the BMI dynamics was -4,33 kg (p<0,001). A decrease in the severity of emotional eating behavior by an average of 0,77 (p<0,001), external eating behavior by 1,05 (p<0,001) points was noted, no significant changes in restrained eating behavior were obtained (p=0,43). According to the CARDIA test, after 2 months of CBGT, the detection rate of pathological significance of BM decreased by 50% (p<0,001); as well as episodes of loss of control over food intake (initially in 5 (25%) (p<0,001)), distress due to loss of control over food intake (initially in 6 (30%) (p<0,001). CBGT in combination with dietary intervention showed a decrease in the severity of chronic stress, which corresponded to an increase in the total score from 1,8±0,75 to 2,0±0,60 (p<0,05), a decrease in vital exhaustion from 5,6±3,89 to 4,1±2,66 (p=0,001) and loneliness from 34,9±12,61 to 29,9±7,57 (p=0,007), a decrease in guilt-proneness from 53,0±8,42 to 42,8±11,18 (p<0,001) and shame-proneness from 38,3±10,99 to 31,6±10,07 points (p=0,014).Conclusion. The mental state of a person has a significant impact on eating behavior and on the regulation of BM, which emphasizes the need for complex interventions to provide effective assistance to people with obesity.